Chromium-based metal-organic framework, MIL-101 (Cr), assisted hydrothermal pretreatment of teff (Eragrostis tef) straw biomass - Ruth Bezabih; Yakob Godebo Godeto; Salah Hamza Sherif; Taju Sani; Ibrahim Nasser Ahmed (Heliyon, 2024)
Teff (Eragrostis tef) is a staple crop and holds the biggest share of grains cultivated area in Ethiopia, consequently, a large quantity of Teff straw is produced. The Teff straw was pretreated for the first time with Chromium-based Metal-Organic Framework, MIL-101(Cr), assisted hydrothermal method at temperatures ranging from 160 to 240 °C for 1/2, 1, or 2 h time independently. With an increase of pretreatment severity, the yield of total reducing sugar (TRS) was increased until reaching maximum (185 mg g−1). The identified optimum hydrothermal pretreatment condition, (180 °C and 1 h), had a feature of higher TRS yield and lower furfural concentration. The morphological analysis showed that treated Teff straw had degraded structure, higher surface area, and distorted bundles than native Teff straws. This study insight into MOFs’ application in lignocellulose biomass processing, and optimizing the pretreatment condition of Teff straw biomass.